Literary journalism - Merljak, Sonja (Acta neophilologica, 2004)
Literary journalism is a style of newspaper and magazine writing that developed as a reaction against factographic and objective journalism. Rather than answering the informational who, what, when, or where, it depicts moments in time. It has also managed to eschew the formula of newspaper feature writing, with its predictability and clichés. Instead, it appointed the techniques of realistic fiction to portray daily life. The author of this paper attempts to present the genre that belongs at the same time to literature and journalism; it combines the best of both practices in order to give the reader the most vivid and accurate picture of society. The author of this paper also attempts to present literary journalism as it exists in Slovenia.
Keywords: American literature; ameriška književnost; literarno novinarstvo; Slovenia; Slovenija; vplivi